Interpretation of the Qur’an and hadith : reflection on some issues - Khan, Israr Ahmad (s.n, 2012)
Islam is not a religion in the modern sense of the word; it is rather complete and comprehensive way of life, guiding mankind in every walk of life including business. The Qur'an and Hadith have both highlighted significance of and rules for business. They view business as the best way to ensure safety and further growth of wealth and property. The present article represents an attempt to explain significance and rules of business as available in the Qur'an and Prophetic tradition